1987
DOI: 10.1016/0378-1097(87)90235-7
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of broad host range plasmids to the type I obligate methanotroph Methylomonas albus

Abstract: SUMMARYPlasmids RP4 (IncP) and R300B (IncQ) (mobilized by RP4) were transferred to Methylomonas albus from Escherichia coli donors at frequencies of 2 × 10 3 and 1-10 3 per donor. BY contrast, plasmids pS-a (IncW) and the IncP plasmids R68.45, R751 and derivatives carrying bacteriophage Mu and/or transposons were transferred to M. albus from E. coli at frequencies of 10 7-10-8 per donor. M. albus transconjugants carrying R68.45, R751 and their derivatives were isolated and used as donors in matings with either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
1992
1992

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Using filter matings, the Inc. P plasmids R68.45, R751, and derivatives carrying bacteriophage Mu and/or transposons and pS-a (Inc W plasmids) were transferred to M. albus from E. Table 1 Plasmids transferred to methanotrophs by conjugation 237 coli at frequencies of 10 -7 to 10 -s. Higher frequencies were noted for RP4 and R300B (10-3). Transfer frequencies for Mu-containing plasmids indicated that the Mu-associated suicide phenomenon did not occur in M. a/bus [53]. In a similar study, AI-Taho and Warner successfully transferred pULBll3, a derivative of RP4 into which a deleted fragment of bacteriophage Mu has been inserted, from E. coli to M. trichosporium OB3b again using filter matings [54].…”
Section: Conjugal Gene Transfer Systemsmentioning
confidence: 85%
“…Using filter matings, the Inc. P plasmids R68.45, R751, and derivatives carrying bacteriophage Mu and/or transposons and pS-a (Inc W plasmids) were transferred to M. albus from E. Table 1 Plasmids transferred to methanotrophs by conjugation 237 coli at frequencies of 10 -7 to 10 -s. Higher frequencies were noted for RP4 and R300B (10-3). Transfer frequencies for Mu-containing plasmids indicated that the Mu-associated suicide phenomenon did not occur in M. a/bus [53]. In a similar study, AI-Taho and Warner successfully transferred pULBll3, a derivative of RP4 into which a deleted fragment of bacteriophage Mu has been inserted, from E. coli to M. trichosporium OB3b again using filter matings [54].…”
Section: Conjugal Gene Transfer Systemsmentioning
confidence: 85%
“…These differences in transfer frequencies could reflect the actual physical efficiencies of the conjugation systems under study. For instance, RP4 is transferred at a frequency of 10-"~/donor from Escherichia colt into Methylomonas albus, but lhe IncW plasmic pSa at a frequency of 10+7/donor [259]. Efficiencies of transfer may a!so be influenced by differential susceptibility of plasmids to the various host-dependent restriction systems since, using the s~me conjugation system, transfer efficieneies of different plasmids into a particular host may vary considerably (1207], see Table 3).…”
Section: Transfer Of Plasmids Iron Methylotrophsmentioning
confidence: 99%
“…suboxydans which could account for the differential transfer frequencies was also considered. McPheat et al [14] have shown a 5-6-fold increase in conjugation frequencies in Methylomonas aibus by subjecting this strain to heat shock (1 min at 50 ° C) before conjugation. However, we were not able to observe a significant increase in conjugation frequencies as a result of heat shock and conclude that a host restriction system does not appear to limit conjugal establishment of broad host range plasmids in G. oxydans ssp.…”
Section: Introduction Of Plasmid Dna Into G Oxydans Spp Suboxydansmentioning
confidence: 99%